عروض مختصرة - أسماء حسين ملكاوي (International Institute of Islamic Thought, 2010)
• القرآن الكريم والقراءة الحداثية دراسة تحليلية نقدية لإشكالية النص عند محمد أركون، الحسن العباقي، دمشق: صفحات للدراسات والنشر، 2009م، 320 صفحة. • أزمة الحضارة العربية المترددة، أبو يعرب المرزوقي، الدوحة: الدار العربية للعلوم ناشرون، مركز الجزيرة للدراسات، 2009م، 71 صفحة. • العولمة وأزمة الليبرالية الجديدة - الكتاب الثاني، محمد عابد الجابري، بيروت: الشبكة العربية للأبحاث والنشر، 2009م، 392 صفحة. • أزمة القيم من مأزق الأخلاقيات إلى جماليات الوجود، جمال مفرج، بيروت: الدار العربية للعلوم ناشرون، 2009م، 95 صفحة. • التعليم وأزمة الهوية الثقافية، محمد عبد الرؤوف عطية، القاهرة: مؤسسة طيبة للنشر والتوزيع، 2009م، 334 صفحة. • Media, Religion and Conflict, By Lee Marsden, and Heather Savigny, London: Ashgate Publishing; Har/Ele edition (October 30, 2009), 184 pages. • Muslims and Media Images: News versus Views, By Ather Farouqui, Oxford University Press, New York: USA (October 11, 2009), 368 • Arab News and Conflict: A Multidisciplinary Discourse Study (Discourse Approaches to Politics, Society and Culture),By Samia Bazzi, John Benjamins Pub Co (October 15, 2009), 240 pages. • Terror Post 9/11 and the Media (Global Crises and the Media), By David L. Altheide, Peter Lang Publishing; First printing edition (July 15, 2009), 232 pages. • Al-Ghazali, Averroes and the Interpretation of the Qur'an: Common Sense and Philosophy in Islam (Culture and Civilization in the Middle East), By Avital Wohlman, Routledge; 1 edition (December 25, 2009), 130 pages. • Al- Ghazali's Philosophical Theology, By Frank Griffel, New York: Oxford University Press, USA (May 28, 2009), 424 pages. • The Qur'an in Its Time (So as Middle East Issues), By Werner Daum, Al Saqi (September 24, 2009), 224 pages. • The East-West dichotomy, By Thorsten Pattberg, New York: LoD Press, (August 18, 2009), 276 pages. • Understanding Muslim Identity: Rethinking Fundamentalism, By Gabriele Marranci, Palgrave Macmillan; 1 edition (February 17, 2009), 242 pages. • God's Continent: Christianity, Islam, and Europe's Religious Crisis (The Future of Christianity), By Philip Jenkins, Oxford University Press, USA; Reprint edition (April 6, 2009), 352 pages. • Was Jesus a Muslim?: Questioning Categories in the Study of Religion, By Robert F. Shedinger, Fortress Press (May 1, 2009), 192 pages. • A Deadly Misunderstanding: A Congressman's Quest to Bridge the Muslim-Christian Divide, By Mark D. Siljander, HarperOne; 1 edition, (October 7, 2008), 272 pages. للحصول على كامل المقالة مجانا يرجى النّقر على ملف ال PDF  في اعلى يمين الصفحة.